Overexpression of Phosphoribosyl Pyrophosphate Synthase Enhances Resistance of Chlamydomonas to Ionizing Radiation - Jung, Sera; Koo, Kwang Min; Ryu, Jaihyunk; Baek, Inwoo; Kwon, Soon-Jae; Kim, Jin-Baek; Ahn, Joon-Woo (Frontiers in Plant Science, 2021)
The enzyme phosphoribosyl pyrophosphate synthase (PRPS) catalyzes the conversion of ribose 5-phosphate into phosphoribosyl diphosphate; the latter is a precursor of purine and pyrimidine nucleotides. Here, we investigated the function of PRPS from the single-celled green alga Chlamydomonas reinhardtii in its response to DNA damage from gamma radiation or the alkylating agent LiCl. CrPRPS transcripts were upregulated in cells treated with these agents. We generated CrPRPS-overexpressing transgenic lines to study the function of CrPRPS. When grown in culture with LiCl or exposed to gamma radiation, the transgenic cells grew faster and had a greater survival rate than wild-type cells. CrPRPS overexpression enhanced expression of genes associated with DNA damage response, namely RAD51, RAD1, and LIG1. We observed, from transcriptome analysis, upregulation of genes that code for key enzymes in purine metabolism, namely ribonucleoside-diphosphate pyrophosphokinase subunit M1, adenylate kinase, and nucleoside-diphosphate kinase. We conclude that CrPRPS may affect DNA repair process via regulation of de novo nucleotide synthesis.